2002
DOI: 10.13031/2013.7855
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties of Dehydrated Apples as Affected by Moisture and Temperature

Abstract: Dielectric properties directly influence microwave drying characteristics of food products. A knowledge of dielectric properties of foods as a function of moisture content and temperature is essential in the design and control of microwave drying systems. Dielectric constant e4 and loss factor e, of Red Delicious apples (Malus domestica Borkh.) were measured over a moisture content range of 4% to 87.5% at 225 C and 605 C. At high moisture content (>70%), free water dispersion and ionic conduction accounted for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
91
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(111 citation statements)
references
References 30 publications
10
91
0
2
Order By: Relevance
“…Various factors influence the dielectric properties of food materials such as frequency of the applied alternating electric field, moisture content, bulk density, temperature (Icier and Baysal 2004b;Nelson 1965;Ryynanen 1995;Venkatesh and Raghavan 2004) ionic nature, concentration (density), structure and constituents of food materials (Engelder and Buffler 1991;Feng et al 2002;Guan et al 2004;Nelson 1991Nelson , 1992Nelson et al 1994;Nelson and Bartley 2002;Ohlsson et al 1974a;Venkatesh and Raghavan 2004;Sipahioglu et al 2003). Dielectric properties as related to temperature and frequencies have been reported for different agricultural commodities, including grains and seeds (Nelson 1965), fruits and vegetables (Feng et al 2002;Guan et al 2004;Ikediala et al 2000;Nelson 1983;Nelson et al 1994;Wang et al 2003), juice and wine (Garcia et al 2004), baked foods and flours (Kim et al 1998;Zuercher et al 1990), dairy products (Green 1997;Herve et al 1998), fish and meat Lyng et al 2005), egg white solutions and thermal denatured egg albumen gels (Lu et al 1998).…”
Section: Factors Affecting the Dielectric Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Various factors influence the dielectric properties of food materials such as frequency of the applied alternating electric field, moisture content, bulk density, temperature (Icier and Baysal 2004b;Nelson 1965;Ryynanen 1995;Venkatesh and Raghavan 2004) ionic nature, concentration (density), structure and constituents of food materials (Engelder and Buffler 1991;Feng et al 2002;Guan et al 2004;Nelson 1991Nelson , 1992Nelson et al 1994;Nelson and Bartley 2002;Ohlsson et al 1974a;Venkatesh and Raghavan 2004;Sipahioglu et al 2003). Dielectric properties as related to temperature and frequencies have been reported for different agricultural commodities, including grains and seeds (Nelson 1965), fruits and vegetables (Feng et al 2002;Guan et al 2004;Ikediala et al 2000;Nelson 1983;Nelson et al 1994;Wang et al 2003), juice and wine (Garcia et al 2004), baked foods and flours (Kim et al 1998;Zuercher et al 1990), dairy products (Green 1997;Herve et al 1998), fish and meat Lyng et al 2005), egg white solutions and thermal denatured egg albumen gels (Lu et al 1998).…”
Section: Factors Affecting the Dielectric Propertiesmentioning
confidence: 99%
“…Dielectric properties as related to temperature and frequencies have been reported for different agricultural commodities, including grains and seeds (Nelson 1965), fruits and vegetables (Feng et al 2002;Guan et al 2004;Ikediala et al 2000;Nelson 1983;Nelson et al 1994;Wang et al 2003), juice and wine (Garcia et al 2004), baked foods and flours (Kim et al 1998;Zuercher et al 1990), dairy products (Green 1997;Herve et al 1998), fish and meat Lyng et al 2005), egg white solutions and thermal denatured egg albumen gels (Lu et al 1998). Studies were also reported that assessed possibility of non-destructively predicting some physical characteristics of agri-food products such as fruits and eggs (Nelson et al 1995;Dev et al 2008).…”
Section: Factors Affecting the Dielectric Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hot air drying has many disadvantages such as lower energy efficiency and long drying times, but despite that it has been used widely [7,8]. Because of the low thermal conductivity of foods, heat transfer to the inner sections during conventional heating is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Como hemos mencionado anteriormente, la frecuencia, temperatura, contenido en sal, humedad, estado del agua (congelada, libre o interaccionando con la matriz) son los principales factores que influyen en las propiedades dieléctricas en materiales biológicos y de la agricultura (Tran et al, 1984; Engelder y Buffler, 1991; Seaman y Seals, 1991;Herve et al, 1998;Berbert et al, 2001;Feng et al, 2002). Içier y Baysal (2004a) realizaron una extensa revisión sobre las propiedades dieléctricas de alimentos, haciendo especial hincapié en los principales factores que afectan a estas propiedades de los alimentos así como a sus posibles usos industriales.…”
Section: Aplicación De La Espectroscopia Dieléctrica Al Control De Caunclassified